2018
DOI: 10.1186/s12870-018-1418-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional study of CHS gene family members in citrus revealed a novel CHS gene affecting the production of flavonoids

Abstract: BackgroundCitrus flavonoids are considered as the important secondary metabolites because of their biological and pharmacological activities. Chalcone synthase (CHS) is a key enzyme that catalyses the first committed step in the flavonoid biosynthetic pathway. CHS genes have been isolated and characterized in many plants. Previous studies indicated that CHS is a gene superfamily. In citrus, the number of CHS members and their contribution to the production of flavonoids remains a mystery. In our previous study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 48 publications
4
65
1
Order By: Relevance
“…In the presence of light, SA treatment significantly increases flavonoid content in Ginkgo biloba leaves [24], which is in agreement with the current study (Figure 1). Similarly, MeJA increases flavonoid accumulation in citrus leaves in the first 12 h after treatment [25], which is slightly different from our observation, possibly due to the differences in elicitors and plant species. Furthermore, we found that exogenous MeSA rapidly and transiently increased PAL activity in tea leaves, which was consistent with the concentrations of flavonoids (Figure 2 and Figure 3).…”
Section: Discussioncontrasting
confidence: 99%
“…In the presence of light, SA treatment significantly increases flavonoid content in Ginkgo biloba leaves [24], which is in agreement with the current study (Figure 1). Similarly, MeJA increases flavonoid accumulation in citrus leaves in the first 12 h after treatment [25], which is slightly different from our observation, possibly due to the differences in elicitors and plant species. Furthermore, we found that exogenous MeSA rapidly and transiently increased PAL activity in tea leaves, which was consistent with the concentrations of flavonoids (Figure 2 and Figure 3).…”
Section: Discussioncontrasting
confidence: 99%
“…Flavonoids are the largest type of secondary metabolites, which are widely distributed in many plants [ 46 , 47 ]. Flavonoids are not only the main compounds that determine the color of flowers, fruits and leaves, but also play an important role in plant growth, development and environmental adaptation [ 48 , 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have diverse biological functions in plant growth, development, and environmental adaptation, including UV protection, antioxidation, defense responses, and attraction of pollinators and animals for seed-dispersal (Winkel-Shirley, 2001; Muhlemann et al , 2018). They also represent major pigments in fruits, leaves, flowers, and seeds, and are beneficial components of the human diet, since they can contribute to the prevention of cardiovascular diseases, cancer (Hou, 2003; Amado et al , 2011), obesity, and diabetes, as well as improve visual function and promote antioxidant and anti-inflammatory activities (Tsuda, 2012; Wang et al , 2018b).…”
Section: Introductionmentioning
confidence: 99%